PENGARUH KEPEMILIKAN INSTITUSI, KARAKTERISTIK DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP PROFITABILITAS - Rizqy Ade Katutari; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2019)
The purpose of this research is the effect of share ownership by institutions, board commissioner characteristics and audit committee character on the profitability of companies in Indonesia in 2016-2017. The sample consists of 61 companies listed in the Indonesia Stock Exchange in 206-2017. The data that was used in this research was secondary data and selected by using purposive sampling method. The analisis method that was used in this research was multiple linear regression. The results of the analysis show that the size of the board of commissioners, the existence of an independent commissioner and the audit committee's financial expertise do not have a significant effect on profitability, the intensity of the board of commissioners meeting and the size of the audit committee have a negative and significant effect on profitability, while the audit committee independence, intensity of audit committee meetings and ownership shares by institutions have a significant positive effect on profitability.